2019
DOI: 10.19045/bspab.2019.80044
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical evaluation of field pea (Pisum sativum L.) landraces under rainfed conditions of AJ&K-Pakistan

Abstract: We investigated the physicochemical attributes of nine pea landraces collected from mountainous areas of Azad Jammu and Kashmir-Pakistan using one cultivar (Meteor) as control. Landraces were grown under the same agro-climatic conditions to remove variance caused by environment × genotype association. There was high physicochemical diversity among the landraces in the content of plant height (23.4-44.7cm), branches per plant(7.55-9.05), flowers/ plant(2-5.32), leaves per plant (31.53-32.80), seeds per pod (3.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Correlation analysis between physical and biochemical attributes of fig can be due to pleiotropic effect or genetic linkage, but previous studies showed that temperature can play an important role (Bashir et al, 2019). Table 4 showed that with decrease in temperature the fruit quality increased which might be due to different environmental factors.…”
Section: Biochemical Attributesmentioning
confidence: 98%
“…Correlation analysis between physical and biochemical attributes of fig can be due to pleiotropic effect or genetic linkage, but previous studies showed that temperature can play an important role (Bashir et al, 2019). Table 4 showed that with decrease in temperature the fruit quality increased which might be due to different environmental factors.…”
Section: Biochemical Attributesmentioning
confidence: 98%